Analysis of User Satisfaction with the Netflix Application as an Entertaiment Medium Using the UX Method - Oktaviola, Yasinta; Rudianto, Christ (Program Studi Sistem Informasi Fakultas Teknik dan Ilmu Komputer, 2024)
This research was conducted to analyze user satisfaction with the Netflix application using the UX Honeycomb method. The UX Honeycomb method is used to evaluate various aspects of user experience, such as usability, aesthetic value, sustainability, accessibility, satisfaction, and diversity. This study involved data collection through online surveys and interviews with active Netflix users. Data analysis was conducted using statistical techniques and qualitative interpretation. The UX Honeycomb method was employed to understand the essential aspects of user experience within the application. The results of this study are expected to provide valuable insights for other streaming service providers to enhance their service quality and create a better user experience. Additionally, the contribution of the UX Honeycomb methodology in assessing user satisfaction can serve as a foundation for further research in the context of digital entertainment applications.